Beyond the Classroom: MOOCs and the Evolution of Lifelong Learning - Anson, Adriel Moses (Journal of Computer Science Application and Engineering (JOSAPEN), 2024)
This study explores the transformative impact of Massive Open Online Courses (MOOCs) on lifelong learning, challenging traditional education paradigms and offering accessible, flexible, and global learning opportunities. Focusing on the dynamics, challenges, and potentials associated with MOOCs, the research emphasizes their role in shaping education beyond conventional classroom settings. The study employs a multidimensional analysis, combining a comprehensive literature review, empirical research methods, and a discussion of findings to provide nuanced insights. Key findings reveal that MOOCs, characterized by massive scalability and interactive features, reach a global audience and engage learners dynamically. However, challenges such as completion rates, learner engagement, quality assurance, access, monetization, and integration persist, necessitating strategic interventions. The study identifies the potential of MOOCs to revolutionize education by offering global accessibility, supporting lifelong learning, accommodating diverse learning styles, integrating innovative technologies, bridging industry-relevant skills gaps, and fostering collaborative learning communities. In conclusion, MOOCs stand at the forefront of the educational landscape, poised to play a pivotal role in the future of education. The article recommends practical strategies for stakeholders to enhance MOOC accessibility, improve learner engagement, address certification concerns, and integrate these platforms into formal education systems. Embracing the transformative power of MOOCs is crucial for building a global learning community that thrives on accessibility, innovation, and continuous learning in the evolving digital era.